Tolcapone Potently Inhibits Seminal Amyloid Fibrils Formation and Blocks Entry of Ebola Pseudoviruses - Qiu, Mengjie (Front Microbiol, 2020)
Ebola virus (EBOV), the causative pathogen of the deadly EBOV disease (EVD), can be transmitted via sexual transmission. Seminal amyloid fibrils have been found enhancers of EBOV infection. Currently, limited preventive vaccine or therapeutic is available to block EBOV infection through sexual intercourse. In this study, we repurpose tolcapone, a US Food and Drug Administration (FDA)-approved agent for Parkinson’s disease, as a potent inhibitor of seminal amyloid fibrils, among which semen-derived enhancer of viral infection (SEVI) is the best-characterized. Tolcapone binds to the amyloidogenic region of the SEVI precursor peptide (PAP248–286) and inhibits PAP248–286 aggregation by disrupting PAP248–286 oligomerization. In addition, tolcapone interacts with preformed SEVI fibrils and influences the activity of SEVI in promoting infection of pseudovirus (PsV) carrying the envelope glycoprotein (GP) of the EBOV Zaire or Sudan species (Zaire PsV and Sudan PsV, respectively). Tolcapone significantly antagonizes SEVI-mediated enhancement of both Zaire PsV and Sudan PsV binding to and subsequent internalization in HeLa cells. Of note, tolcapone is also effective in inhibiting the entry of both Zaire PsV and Sudan PsV. Tolcapone inhibits viral entry possibly through binding with critical residues in EBOV GP. Moreover, the combination of tolcapone with two small-molecule entry inhibitors, including bepridil and sertraline, exhibited synergistic anti-EBOV effects in semen. Collectively, as a bifunctional agent targeting the viral infection-enhancing amyloid and the virus itself during sexual intercourse, tolcapone can act as either a prophylactic topical agent to prevent the sexual transmission of EBOV or a therapeutic to treat EBOV infection.